Development of teacher professionalism in inquiry learning through learning community - Risnanosanti, Risnanosanti; Susyla, Dian; Suyuthie, Hasmi; Mursalin, M; Naziev, Aslanbek; Koklu, Onder; Salcedo, Audy (Electronic Journal of Education, Social Economics and Technology, 2023)
Mechanisms for motivating and involving teachers in learning and working together with their colleagues are currently quite scarce. This study aims to explore the conditions that support teacher professional development in inquiry based learning through learning communities and examine how teacher professional development will impact students learning outcomes. The five teachers selected were a group of teachers who were members of the lesson study community at SMP Negeri 11 Bengkulu city and participated in this study. The qualitative results in this study reveal that the interactive domain, in which the teacher’s professional learning community works collaboratively by sharing teaching experiences and developing assessment tools, plays an important role in promoting teacher professional development. These results reinforce the understanding that conditions and important supporting mechanisms that must be possessed by an effective model for teachers professional development can lead to improved students learning outcomes.